The design and construction of dams including masonry, earth, rock-fill, timber and steel structures also the principal types of movable dams - Wegmann, Edward, 1850-1935 (John Wiley ; Chapman & Hall, 1922)
This study is divided into four parts: the design and construction of masonry dams; earthen, rock-fill, timber, and steel dams; moveable dams, coffer-dams, and overflow weirs; recent dams. It considers examples of structures from around the world.